Effect of MSPO implementation toward farm performance of organized smallholder: a case study in FELDA Lakum, Pahang / Muhammad Mat Ali - Mat Ali, Muhammad (Faculty of Plantation and Agrotechnology, 2019)
Malaysia Sustainable Palm Oil (MSPO) has been developed to ensure sustainability in palm oil cultivation and the supply chain. However, the organized smallholder continues suffer from lower yields but millions of people depend on palm oil for their livelihood. This study is conducted to identify the factors that affect the farm performance of organized smallholders in certified MSPO. A theoretical framework was developed to achieve this objective. A survey was study about an organized smallholder that certified with MSPO. The result of each factor on farm performance of organized smallholders can be identified by using Pearson’s Correlation and Multiple Linear Regression, and with that the crucial factor can be determined. Although best practices policy and economic plan are not improved the farm performance of organized smallholders, indirect effect through environmental management. Further, the certification is needed to improve the criteria in the principle with some of innovation while improving the farm performance of organized smallholders and oil palm plantation.